Chinese Journal of Environmental Law - Chinese Journal of Environmental Law (Brill, 2026)
The Chinese Journal of Environmental Law (CJEL) publishes international, comparative, and national research and reviews concerned with environmental law and policy. While CJEL presents leading work from or concerned with China, other Asian regions, and the developing world at large, the journal’s geographic coverage is unlimited, and its scope is intentionally broad. It encompasses diverse areas of international, regional and national environmental law, including biodiversity law, climate change law, energy law, environmental assessment, marine environmental law, natural resources law, planning law and pollution law, as well as institutional developments such as environmental courts, and compliance and enforcement issues.
FI 0.36
Q4
Keywords: International environmental law; Ciencia ambiental; Leyes; Acuerdos transformativos; Transformative agreements; Política ambiental; Regiones asiáticas; Regiones del mundo